Perceived of Survivors, Families, and Health Professionals on the Recovery Process of Schizophrenia in Indonesia: A Scoping Review - Widianti, Efri; Hidayati, Nur Oktavia; Rafiyah, Imas; Kusumah, Indra (GHMJ (Global Health Management Journal), 2023)
Background: The recovery process of people with Schizophrenia in Indonesia is still not optimal. The lack of success in the recovery process is indicated by the relapse rate in people with schizophrenia, which is still high. Aims: This literature review aims to describe the views of ODS, families, and health workers in the ODS recovery process in Indonesia. Methods: A literature search was carried out using Google Scholar and also The databases PubMed and CINAHL with the keywords Schizophrenia OR psychosis AND family OR Caregiver OR relatives OR care OR spouse OR sibling OR parents AND psychiatrist AND mental health nurse AND mental health professionals AND Perspective OR Perceived AND Recovery AND Indonesia with free-full text criteria in English and Indonesian, and publication time has no limitations. Results: Based on a literature review of 13 articles, different views were obtained between survivors, families, and mental health professionals.  Conclusion: The results of these findings recommend that mental health policymakers consider the views of survivors, families, and health workers regarding recovery in survivors to produce appropriate strategies to help survivors achieve a state of recovery.   Received: 21 November 2023, Revised: 21 December 2023, Accepted: 25 December 2023.